THE IMPACT OF PLACING PRISONERS AND DETAINEES IN ONE ROOM - Ahmad Ubaidillah Assyafii; Odi Jarodi (Universitas Nusa Cendana, 2026)
This study aims to analyze the impact of placing inmates and detainees in the same housing cells at the Class IIA Batam State Detention Center, which is experiencing significant overcrowding. The research uses a qualitative descriptive approach, with data collected through direct observation and in-depth interviews involving inmates, detainees, and correctional staff. The findings reveal that overcrowding combined with the mixing of inmates and detainees creates both physical and psychological pressure. These conditions lead to frustration, discomfort, and the emergence of aggressive behavior among occupants. The lack of separation based on legal status also contributes to tension and reduces the effectiveness of rehabilitation and supervision processes. Although preventive measures have been implemented, the main issues of overcapacity and inadequate classification of detainees have not been fully resolved. Therefore, more comprehensive policies are needed, particularly regarding proper housing classification and capacity management. Future research is recommended to further examine the effectiveness of separation policies and the impact of overcrowding on inmates’ mental health within correctional institutions. Keywords: Deprivation; Frustration-Aggression; Inmate Placement